2018
DOI: 10.15578/jpbkp.v13i2.562
|View full text |Cite
|
Sign up to set email alerts
|

Karakterisasi Biokimia Lektin Makroalga Sargassum polycystum dan Turbinaria ornata/Biochemical Characterisation of Lectin Derived from Sargassum polycystum and Turbinaria ornata Macroalgae

Abstract: Kemampuan lektin untuk mengikat karbohidrat secara spesifik dan reversible dapat dikembangkan dalam berbagai aplikasi, misalnya sebagai reagen histokimia. Penelitian ini bertujuan untuk mempelajari spesifisitas pengikatan lektin makroalga Sargassum polycystum dan Turbinaria ornata pada berbagai jenis karbohidrat, stabilitas aktivitas hemaglutinasi lektin pada berbagai rentang suhu dan pH, serta pengaruh kation divalen pada aktivitasnya. Uji penghambatan hemaglutinasi secara kualitatif dan kuantitatif dilakukan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…However, up till now, report on brown algae lectin is still limited. Only few publications reported the screening of brown algae lectin (Anam, Praseptiangga, Fajarningsih, & Intaqta, 2016;Fajarningsih, Intaqta, Praaseptiangga, Anam, & Chasanah, 2018;Fajarningsih et al, 2015;Freitas et al, 1997;Hung et al, 2012) and to our knowledge only one publication reported the purification of brown algae lectin, an HFL lectin isolated from Hizikia fusiformis (Wu, Tong, Wu, Liu, & Li, 2016). According to Harrysson et al (2018), isolation of lectin or other protein from brown algae is difficult due to the high content of non-protein interfering compounds such as polyphenols and viscous polysaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…However, up till now, report on brown algae lectin is still limited. Only few publications reported the screening of brown algae lectin (Anam, Praseptiangga, Fajarningsih, & Intaqta, 2016;Fajarningsih, Intaqta, Praaseptiangga, Anam, & Chasanah, 2018;Fajarningsih et al, 2015;Freitas et al, 1997;Hung et al, 2012) and to our knowledge only one publication reported the purification of brown algae lectin, an HFL lectin isolated from Hizikia fusiformis (Wu, Tong, Wu, Liu, & Li, 2016). According to Harrysson et al (2018), isolation of lectin or other protein from brown algae is difficult due to the high content of non-protein interfering compounds such as polyphenols and viscous polysaccharide.…”
Section: Introductionmentioning
confidence: 99%